2018
DOI: 10.1177/1541931218621428
|View full text |Cite
|
Sign up to set email alerts
|

The Sooner the Better: Drivers’ Reactions to Two-Step Take-Over Requests in Highly Automated Driving

Abstract: Driving behavior after take-over requests (TORs) is one of the most popular subjects in human factors re-search on highly automated driving. Many studies utilized one-step TOR procedures to prompt drivers to resume vehicle control. The present paper examines driver behavior when experiencing a two-step TOR procedure in different modalities. A two-step TOR gives drivers a choice to resume vehicle controls be-tween a warning (first step) and an alarm (second step). Our findings indicate that a substantial number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This resulted in 171 data points in the first analysis interval and 216 trials in the second analysis interval. For a more detailed analysis of the takeovers, see Epple, Roche, and Brandenburg (2018). Even though all participants took over control, in fourteen trials (6.5%), participants collided with the construction site or drifted from the road.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 171 data points in the first analysis interval and 216 trials in the second analysis interval. For a more detailed analysis of the takeovers, see Epple, Roche, and Brandenburg (2018). Even though all participants took over control, in fourteen trials (6.5%), participants collided with the construction site or drifted from the road.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to imminent situations, scheduled transitions allow for planning within a certain time window. For example, recent works have looked into pre-alerts ("priming" [24]) and multi-stage warnings [5] to improve drivers' TOR responses. However, not many works have addressed the question of when exactly a user interface should communicate a TOR to the driver.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is novel in a way that it aims to determine the potentially best timing to communicate TORs to drivers. Such a system could become a valuable extension for in-vehicle interfaces, e.g., for multi-stage TORs [5]. Although the challenge of determining an appropriate timing to interrupt drivers has been proposed by empirical works both in the context of side activities [22] and transitions [28], we are not aware of any project investigating how such interfaces could be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there have been substantial numbers of studies to design effective TOR signals. Regarding the channel or modality of the signal, for example, Epple et al and Walch et al revealed that drivers preferred a combination of visual, auditory and tactile cues for the TOR signal rather than the use of a single channel (Epple et al, 2018;Walch et al, 2015). Moreover, a combination of generic sounds and speech sounds can trigger the fastest drivers' response time (Forster et al, 2017).…”
Section: Introductionmentioning
confidence: 99%